2009
DOI: 10.1007/s10641-009-9534-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of phenotypic plasticity and local adaption in metabolic rates between components of the Icelandic cod (Gadus morhua L.) stock

Abstract: Phenotypic plasticity and local adaptations are important considerations in delineating population structure of marine fishes and critical to their conservation and management. We compared the weight-specific oxygen consumption rates (VO 2 /M) of juvenile cod from the northern and southern components of the Icelandic stock acclimated to 4.0°C, 8.5°C, and 12.6°C and their metabolic response to abrupt temperatures changes within this range. Southern individuals exhibited VO 2 /M up to 50% higher than their north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…A large thermal gradient exists between these 2 areas (Brander 1994) and Bradbury et al (2010) showed that cod from the southern population have mostly 'warmer' tempe ratureassociated SNPs (single nucleotide polymorphisms), while cod from the Newfoundland and Labrador population have mostly 'cold' alleles. These polymorphisms may be partly responsible for the differences in several phenotypic traits, such as growth (Purchase & Brown 2000, 2001, Salvanes et al 2004, Harrald et al 2010, juvenile food conversion efficiency (Purchase & Brown 2000), morphology and allometry (Marcil et al 2006) and metabolic plasticity to temperature (Grabowski et al 2009), among Atlantic cod populations. Some of these pheno typic changes are considered an example of countergradient variation (CnGV), which occurs when genotypes oppose envi-ronmental influences, leading to reduced phenotypic variation along a gradient (as reviewed by Conover et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large thermal gradient exists between these 2 areas (Brander 1994) and Bradbury et al (2010) showed that cod from the southern population have mostly 'warmer' tempe ratureassociated SNPs (single nucleotide polymorphisms), while cod from the Newfoundland and Labrador population have mostly 'cold' alleles. These polymorphisms may be partly responsible for the differences in several phenotypic traits, such as growth (Purchase & Brown 2000, 2001, Salvanes et al 2004, Harrald et al 2010, juvenile food conversion efficiency (Purchase & Brown 2000), morphology and allometry (Marcil et al 2006) and metabolic plasticity to temperature (Grabowski et al 2009), among Atlantic cod populations. Some of these pheno typic changes are considered an example of countergradient variation (CnGV), which occurs when genotypes oppose envi-ronmental influences, leading to reduced phenotypic variation along a gradient (as reviewed by Conover et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, most studies try to control for previous environmental history by either using the F 1 generation of cultured fish (e.g. Grabowski et al 2009) or allowing individuals to acclimate to a common garden environment (e.g. Harrald et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The species exhibits wide variation in life history traits, and populations often include individuals that exhibit sedentary or resident behaviour (i.e., individuals that do not migrate; Green and Wroblewski 2000;Robichaud and Rose 2004;Neat et al 2006), as well as individuals that migrate seasonally to and from feeding or overwintering grounds with a degree of spawning site fidelity (Jónsson 1996;Ruzzante et al 2000;Pampoulie et al 2006), and also individuals that differ in spawning behaviour and growth -metabolic reaction norms (Hutchings et al 2007;Grabowski et al 2009). Little, if any, of this knowledge has historically been integrated into fisheries management.…”
Section: Introductionmentioning
confidence: 99%
“…Atlantic cod Gadus morhua L. 1758 is such an example of a broadcast spawning species that seems to exhibit fine‐scale population structuring within management units based on differences in behaviour, physiology, growth and reproduction (Salvanes et al , 2004; Jónsdóttir et al , 2006; Pampoulie et al , 2006; Hutchings et al , 2007; Knutsen et al , 2007; Pardoe et al , 2008; Grabowski et al , 2009). Failure to account for such diversity and structure within management units has been suggested as a contributing factor in the decline or collapse of several stocks (Hutchings & Reynolds, 2004; Hutchinson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite analysis has revealed genetic discontinuities between fishes north and south of Iceland, as well as between shallow (<200 m) and deep (>200 m) spawning areas in southern Iceland (Pampoulie et al , 2006). The geographic differentiation seems to be associated with differences in growth and metabolic responses to temperature (Grabowski et al , 2009; Libungan, 2010), while the genetic differentiation associated with spawning depth may be related to ecological and behavioural divergences (Grabowski et al , 2011). Data recovered from electronic data storage tags (DST) indicate at least two distinct types of behaviour in Icelandic G. morhua (Pálsson & Thorsteinsson, 2003; Pampoulie et al , 2008; Grabowski et al , 2011).…”
Section: Introductionmentioning
confidence: 99%